Środowiskowy kontekst niedostosowania społecznego uczniów szkół ponadgimnazjalnych w Głogowie - Ilnicka, Renata
The subject of the paper corresponds to the social disability and specially to the role of sociocultural factors influencing the students behaviour in post gimnazjum schools.
Keywords: Głogów; młodzież; niedostosowanie społeczne; socjalizacja